Literatur Review : Rapid Immunochromatography Sebagai Metode Skrining Kanker Serviks Berbasis Deteksi Onkoprotein HPV pada Urin - Ika Rahmawati Sutejo; Kiky Martha Arieska (Politeknik Negeri Jember, 2020)
Cervical cancer is still become main health problem especially in development country. This cancer is the second most common cancer in Indonesian women. It commonly caused by infection of Human Papillomavirus (HPV) type 16 and 18. Actually if cervical cancer was detected earlier, it shows better respond therapy than other cancers, but this opportunity is not supported by appropiate screening methods. Nowadays, pap smear and IVA are commonly used for detect cervical cancer but they only recommend for women who have had sexual intercourse. Both of them also require medical expertise and pap smear is highly cost. Based on these problem, this paper describes novel method for cervical cancer screening by using rapid immunochromatography kit which is more applicative, noninvasive, and affordable. This paper was a literature review (library research). Data obtained through the search engine using keywords: